"They're a little bit squeezed in the middle": Strategic challenges for innovation in US Metropolitan newspaper organisations. Issue 1 (2nd January 2020) - Villi, Mikko; Grönlund, Mikko; Linden, Carl-Gustav; Lehtisaari, Katja; Mierzejewska, Bozena; Picard, Robert G.; Roepnack, Axel
ABSTRACT: This paper focuses on media innovation among publishers of metropolitan newspapers in the United States, in cities such as San Diego, Boston, Miami, Philadelphia and Dallas. The situation for metropolitan newspapers is difficult, as they fall between national newspapers, which can aim for extending their reach both nationally and globally, and local newspapers, which have a smaller cost structure and can cater to a more limited, and often more engaged, audience community. Our paper demonstrates that there seems to be great awareness of what can be done by US metropolitan newspapers, but managers are struggling with constraints, such as lack of financial and human resources and general organisational anaemia.